The Effect of Layer Thickness and Orientation of the Workpiece on the Micro- and Macrogeometric Properties and the Machining Time of the Part during 3D Printing - Kónya, Gábor; Ficzere, Péter (Periodica polytechnica. Mechanical engineering - Mas̆inostroenie, 2023)
3D printing technologies have developed significantly over the last 30 years, with a major impact on all segments of today's industry. With the introduction of additive manufacturing, product development time can be greatly reduced and printing functional parts directly is also a viable option. Another advantage of additive manufacturing is that it allows greater design freedom than traditional manufacturing technologies. This makes it possible to print products with complex geometries and even different material qualities. In this paper, the authors investigated the effects of printing time, the layer thickness and the orientation on the surface roughness and cylindricity of the printed parts. The aim is to find the combination of layer thickness and part orientation which causes the best results in terms of surface roughness and cylindricity as a function of printing time.